2021
DOI: 10.3390/foods10102397
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Extrudates Based on Rapeseed and Pea Protein Blends Using High-Moisture Extrusion Cooking

Abstract: Rapeseed protein is not currently utilized for food applications, although it has excellent physicochemical, functional, and nutritional properties similar to soy protein. Thus, the goal of this study was to create new plant-based extrudates for application as high-moisture meat analogs from a 50:50 blend of rapeseed protein concentrate (RPC) and yellow pea isolate (YPI) using high-moisture-extrusion (HME) cooking with a twin-screw extruder to gain a better understanding of the properties of the protein powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…The bibliometric analysis revealed that the 84 papers included in the systematic review were published in 38 journals between 1972 and 2022. It was revealed that the most frequent journals chosen by the authors were Foods with 15 articles [ 14 , 15 , 24 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], followed by Journal of Food Science with nine articles [ 11 , 20 , 25 , 60 , 61 , 62 , 63 , 64 , 65 ]. Because the journals were indexed by both Scopus and Web of Science databases, they were all of high quality, and most were placed in Quartile 1 or 2 (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The bibliometric analysis revealed that the 84 papers included in the systematic review were published in 38 journals between 1972 and 2022. It was revealed that the most frequent journals chosen by the authors were Foods with 15 articles [ 14 , 15 , 24 , 41 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], followed by Journal of Food Science with nine articles [ 11 , 20 , 25 , 60 , 61 , 62 , 63 , 64 , 65 ]. Because the journals were indexed by both Scopus and Web of Science databases, they were all of high quality, and most were placed in Quartile 1 or 2 (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because various plants have varying protein types and qualities, numerous efforts have been made to create a novel blend of several plant proteins with the hope that some proteins may compensate for the drawbacks of other plant proteins during the texturization process. For example, Kozlowska et al [ 81 ] and Zahari et al [ 14 ] suggested that rapeseed protein would be a good source for supplementing other vegetable proteins, e.g., soybean and yellow pea. Arueya et al [ 67 ] created meat analogues from Lima bean protein concentrate (LBPC) and African oil bean seed concentrate (AOBSPC), which are underutilized legumes with high nutritional potential grown mainly in Peru.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations